TIFA promotes colorectal cancer cell proliferation in an RSK‐ and PRAS40‐dependent manner. Issue 9 (14th June 2022) - Shen, Wenzhi; Du, Wenfei; Li, Yanping; Huang, Yongming; Jiang, Xinyu; Yang, Chenglong; Tang, Jiaping; Liu, Huan; Luo, Na; Zhang, Xiaoyuan; Zhang, Zhixin
Abstract: Previous studies have reported that TIFA plays different roles in various tumor types. However, the function of TIFA in colorectal cancer (CRC) remains unclear. Here, we showed that the expression of TIFA was markedly increased in CRC versus normal tissue, and positively correlated with CRC TNM stages. In agreement, we found that the CRC cell lines show increased TIFA expression levels versus normal control. The knockdown of TIFA inhibited cell proliferation but had no effect on cell apoptosis in vitro or in vivo. Moreover, the ectopic expression of TIFA enhanced cell proliferation ability in vitro and in vivo. In contrast, the expression of mutant TIFA (T9A, oligomerization site mutation; D6, TRAF6 binding site deletion) abolished TIFA‐mediated cell proliferation enhancement. Exploration of the underlying mechanism revealed that the protein synthesis‐associated kinase RSK and PRAS40 activation were responsible for TIFA‐mediated CRC progression. In summary, these findings suggest that TIFA plays a role in mediating CRC progression. This could provide a promising target for CRC therapy. Abstract : We discovered that TIFA promotes cell proliferation in CRC cell line in vitro and in a xenograft nude mouse model in vivo. We revealed that TIFA mediates RSK and PRAS40 activation to facilitate protein synthesis which relied on TIFA oligomerization (T9) and TRAF6 binding (E178) in vitro and in vivo. We also demonstrated that RSK inhibitor and PRAS40 shRNAs which prevent RSK and PRAS40 activation could suppress TIFA mediated CRC cell proliferation significantly.